Bilingualism and Its Implications for Neuropsychological Evaluation. (27th March 2021) - Paplikar, Avanthi; Alladi, Suvarna; Varghese, Feba; Mekala, Shailaja; Arshad, Faheem; Sharma, Meenakshi; Saroja, Aralikatte Onkarappa; Divyaraj, Gollahalli; Dutt, Aparna; Ellajosyula, Ratnavalli; Ghosh, Amitabha; Iyer, Gowri K; et al.
Abstract: Objective: In the background of a large population of bilinguals globally, the study aimed to develop standards of neuropsychological testing in the context of bilingualism. Because bilingualism is known to affect cognitive processes, bilinguals and monolinguals were compared on their performance on cognitive tests, to investigate the possibility of the need for separate normative data for the two groups. Method: A comprehensive neuropsychological test battery, standardized across five Indian languages: the Indian Council of Medical Research-Neuro Cognitive Tool Box (ICMR-NCTB) was administered to 530 participants (267 monolingual and 263 bilinguals matched for age and education). A systematic method of testing cognition in bilinguals was developed; to identify the appropriate language for testing, ensure language proficiency of examiner, and to interpret the bilingual responses. Additionally, the performance of bilinguals on the ICMR-NCTB was compared with monolinguals. Results: Cognitive testing in the bilingual context was performed in the most proficient language of the participants, by examiners well versed with the language. Results from the language-based tests suggested that the frequent occurrence of borrowed- and language-mixed words required consideration while scoring. The reported bilingual effect on cognitive processes did not reflect as differences in the performance between bilinguals and monolinguals. Conclusions: Observations from the study provide robust recommendations for neuropsychological testing in the context of bilingualism. Results indicate that separate normative data may not be required for bilinguals and monolinguals. The study will be relevant and provide a reference framework to address similar issues in the large population of bilinguals in other societies.